2019 eCITRA : Digital X Culture - Mohamad Faizuan, Bin Mat (2019)
eCITRA is a flagship visual arts exhibition organized by Faculty of Applied & Creative Arts, UNIMAS. Where, in 2019 it is realized at National Art Gallery, Kuala Lumpur with the theme Digital X Culture and it was curated by Mohamad Faizuan Bin Mat & Siti Shahida Kamel.